1994
DOI: 10.1038/icb.1994.23
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer and natural cytotoxic cells are present at the maternal‐fetal interface during murine pregnancy

Abstract: Summary NK cell activity has been detected in the early murine decidua, and hypothesized to be mediated by granulated metrial gland (GMG) cells. The possibility that natural cytotoxic (NC) cells are also present in the decidua has not been investigated. In this study mAb to NK cells (anti‐NK‐1.1) and NC cells (anti‐NC‐1.1) were used to characterize the decidual cells of days 8–14 pregnant (CBAxC57BL/6) Fl mice. Flow cytometric and immunohistological analyses showed predominantly NK‐1.1+ and NC‐1.1+ large and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…Natural cytotoxic cells are defined by their ability to lyse Wehi 164 cells, a mouse fibrosarcoma cell line [17], although the recognition molecules which initiate this activity remain to be established. Earlier results from our own laboratory of NK cytotoxic activity in metrial gland cell suspensions [12,13] do not accord with the findings of Clarke et al [16]. However, we report here on our studies of NC activity in cell suspensions which contain GMG cells prepared from mouse metrial glands, and also from rat metrial glands which have not previously been assessed for NC cell cytotoxic activity.…”
Section: Introductioncontrasting
confidence: 92%
“…Natural cytotoxic cells are defined by their ability to lyse Wehi 164 cells, a mouse fibrosarcoma cell line [17], although the recognition molecules which initiate this activity remain to be established. Earlier results from our own laboratory of NK cytotoxic activity in metrial gland cell suspensions [12,13] do not accord with the findings of Clarke et al [16]. However, we report here on our studies of NC activity in cell suspensions which contain GMG cells prepared from mouse metrial glands, and also from rat metrial glands which have not previously been assessed for NC cell cytotoxic activity.…”
Section: Introductioncontrasting
confidence: 92%
“…Mitogenic response is decreased during pregnancy. Natural killer cell activity decreases as estrogen levels rise; therefore, this protective mechanism would be predicted to be at its lowest efficiency during pregnancy (6,8,19). Finally, local secretion of Igs is influenced by estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta is rapidly developing more intimate contact between the maternal and fetal circulations to support this growth (9). Development of the metrial gland and maximal numbers of pregnancy-associated granulated metrial gland cells also occur around gd 14 (6,8,12,19).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro characterization of the type of cytotoxic activity expressed by cells from the uterine wall of pregnant mice 4 and rats 5 revealed they were cytotoxic to Wehi 164 fibrosarcoma cells (the targets for natural cytotoxic (NC) activity); the effector cells were identified as GMG cells 5 . In addition, cells isolated from metrial glands of pregnant rats were shown to express antibody‐dependent cellular cytotoxic (ADCC) activity 6 .…”
Section: Introductionmentioning
confidence: 99%